IVAN VAHYLEVYCH’S GRAMMAV OF THE UKRAINIAN LAHGUAGE - Lesiuk, M. P. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The paper analyzes the outstanding linguistic work “Grammar of the Ruthenian language in Galicia” by Ivan Vahylevych, a famous Galician poet, ethnographer and philologist. It considers that this research had played a certain role in the development of literary language in Galicia, even though it was written in Polish and was affected greatly by the Russian grammar books. However, it contains valuable illustrative materials which reflect the language of the people in Galicia in the middle of 19th century.